Encountering the “Other”: The Search for Indigenous Identity in Québécois Cinema - Bertrand, Karine; MacKenzie, Scott (Nouvelles vues, 2022)
The relationship between Québécois cinema, memory and territory has existed for decades. This article demonstrates how Indigenous peoples continue to occupy an important space in the economy of representations (real and imagined) situated within Québécois cinema. In recent years, contemporary documentaries that address Indigenous peoples such as Québékoisie (Mélanie Carrier and Olivier Higgins, 2014) and L’empreinte (Carole Poliquin, 2015), have changed their general tone (at least superficially) but have nonetheless extended the image which positions the Amérindien as a mirror for the fraught identity of the French-Canadians living in Québec. Through the analysis of both contemporary Indigenous and non-Indigenous films, this article identifies the configurations of this quest for Indigenous identity in Québécois documentary films and in Arnait Video Production films, through the reconfiguration and re-imagination of intercultural relationships.